First description of the male of Lycodon irwini Naveen, Zeeshan, Mirza, Choure & Chandramouli, 2025 (Squamata: Colubridae), with an updated account of the herpetofauna of the Great Nicobar Islands, India - Nguyen, Tan Van; Harikrishnan, Surendran; Ray, Sumidh; Mohapatra, Pratyush P.; Poyarkov, Nikolay A.; David, Patrick (Zootaxa, 2026)
Lycodon irwini Naveen, Zeeshan, Mirza, Choure & Chandramouli, 2025 was recently described from three female specimens collected in the Nicobar Islands, India. Until now, no male individuals had been reported, leaving potential sexual dimorphism and several diagnostic characters insufficiently understood. Here, we provide the first morphological description of the male and refine the species diagnosis using information from both sexes. In addition, an updated identification key to the species of the Lycodon subcinctus complex is presented. We also compile an updated checklist of 74 species of amphibians and reptiles recorded from the Nicobar Islands.